2020
DOI: 10.5194/acp-20-4713-2020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vessel characteristics and atmospheric processes on the gas and particle phase of ship emission plumes: in situ measurements in the Mediterranean Sea and around the Arabian Peninsula

Abstract: Abstract. A total of 252 emission plumes of ships operating in the Mediterranean Sea and around the Arabian Peninsula were investigated using a comprehensive dataset of gas- and submicron-particle-phase properties measured during the 2-month shipborne AQABA (Air Quality and Climate Change in the Arabian Basin) field campaign in summer 2017. The post-measurement identification of the corresponding ship emission events in the measured data included the determination of the plume sources (up to 38 km away) as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
5
36
0
Order By: Relevance
“…This indicates that the direct biogenic acetaldehyde emissions from the ocean are probably insufficient to explain the measured acetaldehyde. More likely, acetaldehyde and other small carbonyl compounds can be formed in the sea, especially in the surface microlayer (SML) via photodegradation of coloured dissolved organic matter (CDOM) (Kieber et al, 1990;Zhou and Mopper, 1997;Ciuraru et al, 2015). Zhou and Mopper (1997) calculated the exchange direction of small carbonyls based on measurement results and identified that the net flux of acetaldehyde was from the sea to the air, whereas formaldehyde was taken up by the sea.…”
Section: Oceanic Emissionmentioning
confidence: 99%
“…This indicates that the direct biogenic acetaldehyde emissions from the ocean are probably insufficient to explain the measured acetaldehyde. More likely, acetaldehyde and other small carbonyl compounds can be formed in the sea, especially in the surface microlayer (SML) via photodegradation of coloured dissolved organic matter (CDOM) (Kieber et al, 1990;Zhou and Mopper, 1997;Ciuraru et al, 2015). Zhou and Mopper (1997) calculated the exchange direction of small carbonyls based on measurement results and identified that the net flux of acetaldehyde was from the sea to the air, whereas formaldehyde was taken up by the sea.…”
Section: Oceanic Emissionmentioning
confidence: 99%
“…Low-NO x environments such as the clean MBL and the lower free troposphere are considered net O 3 destruction regimes, whereas the upper troposphere and areas with anthropogenic emissions of O 3 precursors are considered regions of net O 3 production (Klonecki and Levy, 1997;Bozem et al, 2017). Measurements performed in the Houston Ship Channel revealed NOPRs of the order of several tens of part per billion per hour (Chen et al, 2010;Ren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Asia, India and the Middle East, NO x emissions have substantially increased during the last decade so that the global NO x burden has essentially remained constant (Miyazaki et al, 2017). NO x emissions from ocean-going vessels have attracted considerable attention, as they are reported to account for 15 % of the global NO x emission burden (Celik et al, 2020). Model calculations suggest that the Arabian Gulf, with an estimated annual NO x emission density of about 1 ton km −2 from ship traffic, is among the regions with the highest NO x emission densities worldwide (Johansson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The slope is similar to that derived by Celik et al (2020) (2.7 ± 0.8) who examined single ships plumes in a more detailed analysis and with literature values that range from 6.8 ± 6.3 near the coast of Texas (Williams et al, 2009) to 11.2 ± 10.9 (Diesch et al, 2013) at the Elbe river near Hamburg/Germany. In comparison to Celik et al (2020), however, the two other literature studies only sampled very fresh and unprocessed ship plumes, from a distance of less than ca. 5 kilometres to the emission source.…”
Section: Lifetime and Sources Of Noxmentioning
confidence: 99%